The Influence of Poetry Appreciation on Spiritual Intelligence and Hedonistic Behavior - Santika, Santika; Purwanto, Edy; Mugiarso, Heru (Universitas Negeri Semarang, 2023)
Hedonistic behavior refers to attitudes that prioritize pleasure, spending time outside the home, playing more, and enjoying the hustle and bustle of the city solely for the sake of pleasure, which result in negative behavior. Therefore, this study aimed to analyze the influence of poetry appreciation on spiritual intelligence and hedonistic behavior. It was a quantitative study which used a correlational design and involved a total of 390 respondents as the study sample. Their data were collected using the instruments of the Attitudes to Beauty Scale (EBS), the Spiritual Intelligence Self-Report Inventory (SISRI-24), and the Female Hedonistic Behavior Questionnaire (FHBQ). Following the data collection and analysis, it was found that poetry appreciation significantly influenced spiritual intelligence. Furthermore, poetry appreciation had a significant indirect influence through the mediation of spiritual intelligence on hedonistic behavior. Based on these findings, it is recommended that counselors utilize and encourage students to assess and understand life phenomena expressed in poetry to enhance spiritual intelligence and reduce hedonistic behavior.